A new way forward or the old way back? counterinsurgency in the Iraq surge - Buchanan, Matthew T. (2018)
This work will consist of three chapters and a conclusion. The goal is to explain the need for the Surge, its image, and its relative success. Many of the histories written about the Surge appear within the first three years of the operation. Over a decade has passed since the start of the Surge in early 2007, and sources have come to light that did not exist in the immediate aftermath. Using these sources involves looking at the events that made the Surge a viable option, the political policy used in Iraq, and the tactical strategy employed by the US military and coalition forces. Also, new evidence allows for previous claims of success to be analyzed in a nuanced way and draw conclusions about the long-term strengths and weaknesses of the Surge.